Advances in the study of behavior. - Slater, P. J. B. (Peter James Bramwell), 1942- (Advances in the study of behavior., 1997)
Advances in the Study of Behavior continues to serve scientists across a wide spectrum of disciplines. Focusing on new theories and research developments with respect to behavioral ecology, evolutionary biology, and comparative psychology, these volumes foster cooperation and communication in these diverse fields.